Modulation of Hypoxia-Inducible Factors and Vascular Endothelial Growth Factor Expressions by Superfood Camu-Camu (Myrciaria dubia) Treatment in ARPE-19 and Fetal Human RPE Cells - Ayaka Nakai; Deokho Lee; Chiho Shoda; Kazuno Negishi; Hiroyuki Nakashizuka; Satoru Yamagami; Toshihide Kurihara (Journal of Ophthalmology, 2023)
Background. Anti-vascular endothelial growth factor (anti-VEGF) therapy via intravitreal injection is an effective treatment for patients with abnormal ocular neovascularization, such as age-related macular degeneration (AMD) and diabetic macular edema (DME). However, prolonged and frequent anti-VEGF treatment is associated with a risk of local and systemic adverse events, including geographic atrophy, cerebrovascular disease, and death. Furthermore, some patients do not adequately respond to anti-VEGF therapy. Hypoxia-inducible factor (HIF) is a transcription factor that controls the expression of hypoxia-responsive genes involved in angiogenesis, inflammation, and metabolism. The HIF/VEGF pathway plays an important role in neovascularization, and the inhibition of HIF activation could be an effective biomolecular target for neovascular diseases. The demand for disease prevention or treatment using functional foods such as superfoods has increased in recent years. Few reports to date have focused on the antineovascular effects of superfoods in the retinal pigment epithelium (RPE). In light of the growing demand for functional foods, we aimed to find novel HIF inhibitors from superfoods worked in RPE cells, which could be an adjuvant for anti-VEGF therapy. Methods. Seven superfoods were examined to identify novel HIF inhibitor candidates using luciferase assay screening. We used the human RPE cell line ARPE-19 and fetal human RPE (fhRPE) to investigate the biomolecular actions of novel HIF inhibitors using quantitative PCR and western blotting. Results. Under CoCl2-induced pseudohypoxic condition and 1% oxygen hypoxic incubation, camu-camu (Myrciaria dubia) showed HIF inhibitory effects determined by luciferase assays. Camu-camu downregulated HIF-1α and VEGFA mRNA expressions in a concentration-dependent manner. Camu-camu also inhibited HIF-1α protein expressions, and its inhibitory effect was greater than that of vitamin C, which is present at high levels in camu-camu. Conclusion. The camu-camu extract suppressed the activation of HIF and VEGF in RPE cells. This could assist anti-VEGF therapy in patients with abnormal ocular neovascularization.